Effects of Erythroxylum Cuneatum (Miq.) Kurz on cellular and synaptic adaptation of chronic morphine-addicted human neuroblastoma cell line at protein level - Sulaiman, Noor Azuin (2017)
Erythroxylum cuneatum (E. cuneatum) is a tropical flowering plant listed under Erythroxylaceae family. E. cuneatum is widely distributed within Southeast Asia. Uses of E. cuneatum in alternative medicines or remedies are limited. Indigenous traditional healer claimed that the plant was used in treating drug withdrawal. However, there is no scientific data to support the claim. Thus, the study was designed to evaluate the potential of anti-withdrawal properties of alkaloid extract of the plant on chronic morphine-addicted cell. An alkaloid extract of E. cuneatum (designated as ECAl) was extracted for all the tests. The human neuroblastoma cell line, SK-N-SH, was used throughout the study. The effects of ECAl on the chronic morphine-addicted cell were observed in two different groups, the co- and pre-treatments of morphine. Throughout the study, ECAl (0.1, 0.5, and 1.0 μg/mL) was compared to morphine and methadone. The receptor involved for the effects of the plant was determined using antagonists. The expressions of Cyclic adenosine 3', 5'-monophosphate (cAMP), intracellular calcium ion ([Ca2+]i), and α-synuclein were studied. At the beginning of the study, withdrawal markers [α-synuclein and calmodulin] were observed, followed by the receptor trafficking [Vesicle-associated membrane protein 2 (VAMP 2) and synaptotagmin 1], desensitisation or internalisation of the receptor [G protein-coupled receptor kinases (GRK) 2, β-arrestin 1/2, and clathrin], and cellular adaptation [mitogen-activated protein(MAP)/extracellular signal-regulated (ERK) kinase (MEK) 1/2, ERK 2, cAMP- dependent protein kinase (PKA), and protein kinase C (PKC)] affected by the ECAl. Through the receptor affinity studies, ECAl bound to μ-opioid receptor, similar to methadone and morphine. Present data showed that ECAl possesses anti-withdrawal properties. ECAl was observed to enhance the receptor trafficking and cause the internalisation of the receptor. The cellular and synaptic adaptations modulated by ECAl were consistent throughout all study and parallel with the effects of the methadone. The administration of ECAl at the optimal doses was postulated to minimise the withdrawal, dependence, and tolerance against morphine-addicted cell. The alkaloid extract of the plant has a potential in opioid substitution therapy.